Do managers manage earnings to 'just meet or beat' analyst forecasts?. Evidence from Australia - Habib, A.; Hossain, Mahmud (Pergamon, 2008)
This paper examines whether managers manage earnings to ‘just meet or beat’ analyst forecasts in Australia. Previous Australian studies on benchmark-beating have focused on loss avoidance and small earnings increases as benchmarks [Coulton, J., Taylor, S., & Taylor, S. (2005). Is ‘benchmark beating’ by Australian firms evidence of earnings management? Accounting and Finance, 45, 553–576; Holland, D., & Ramsay, A. (2003). Do Australian companies manage earnings to meet simple earnings benchmarks? Accounting and Finance, 43, 41–62]. This paper extends this earlier research on benchmark-beating in Australia by incorporating analyst forecast as an important benchmark. Using three different models of unexpected accruals as proxies for earnings management, this study did not find any significant difference between the mean and median unexpected accruals of the “‘just meet or beat” group as against the “just miss” group. Furthermore, for a long period of time (1997–2002), the proportion of Australian firms ‘just meeting or beating’ analyst forecasts benchmark increased, although such increase was not statistically significant.